2015
DOI: 10.3144/expresspolymlett.2015.85
|View full text |Cite
|
Sign up to set email alerts
|

Novel electrically conductive polyurethane/montmorillonite-polypyrrole nanocomposites

Abstract: Abstract. This work describes the production of electrically conductive nanocomposites based on thermoplastic polyurethane (TPU) filled with montmorillonite-dodecylbenzenesulfonic acid-doped polypyrrole (Mt-PPy.DBSA) prepared by melt blending in an internal mixer. The electrical conductivity, morphology as well as the rheological properties of TPU/MtPPy.DBSA nanocomposites were evaluated and compared with those of TPU nanocomposites containing different conductive fillers, such as polypyrrole doped with hydroc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
19
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 60 publications
(78 reference statements)
4
19
1
Order By: Relevance
“…This layered morphology results in a higher aspect ratio and surface area (3.52 m 2 g -1 ) 42 than found for the spherical particles of PPy (2.06 m 2 g -1 ) 42 , and consequently increases the interaction of Mt-PPy with the PBAT matrix and thus improves its ability to form a conductive network in the matrix. Similar results have been reported by Ramoa et al 35 for thermoplastic polyurethane (TPU) filled with Mt-PPy and PPy. Also, Contri et al 43 and Vargas et al 41 have found similar results for epoxy and thermoset polyurethane, respectively, with the same nanoparticles.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…This layered morphology results in a higher aspect ratio and surface area (3.52 m 2 g -1 ) 42 than found for the spherical particles of PPy (2.06 m 2 g -1 ) 42 , and consequently increases the interaction of Mt-PPy with the PBAT matrix and thus improves its ability to form a conductive network in the matrix. Similar results have been reported by Ramoa et al 35 for thermoplastic polyurethane (TPU) filled with Mt-PPy and PPy. Also, Contri et al 43 and Vargas et al 41 have found similar results for epoxy and thermoset polyurethane, respectively, with the same nanoparticles.…”
Section: Resultssupporting
confidence: 90%
“…The absorption bands centered at 1730 and 1710 cm -1 are attributed to the free and site-specific interactions of the carbonyl group, respectively. The interaction between PBAT and PPy can be determined from the ratio between free carbonyl absorption bands indicates that a site-specific interaction between N-H and C=O functional groups is operative in both polymer systems 35 . Figure 6 (a, b) shows the variation in the storage modulus (E') and loss tangent (tan δ) as a function of temperature for neat PBAT, PBAT/Mt-PPy and PBAT/PPy.…”
Section: Resultsmentioning
confidence: 99%
“…Nowadays, already a large body of works addressed the preparation and characterization of shape memory PUs (SMPUs) [13][14][15][16]. Research strategies focus now on the creation of multifunctional polymers [17,18]. As far as SM concerns, attempts are in progress to combine it with self-healing [19].…”
Section: Introductionmentioning
confidence: 99%
“…Although the interest in polymer/layered silicate nano composites has ebbed somewhat recently, relatively intensive work is going on in the field and a large number of papers are published [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. The decrease of interest is caused by the fact that the nano hype has not been justified and a breakthrough has not occurred in the application of such composites.…”
Section: Introductionmentioning
confidence: 99%